PENINGKATAN HASIL BELAJAR DENGAN MENERAPKAN METODE PEMBERIAN TUGAS BERBANTUAN KARTU BILANGAN PADA PEMBELAJARAN MATEMATIKA - Arman, Arman; Margiati, K. Y.; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research aimed to determine learning outcome of students in mathematics that used the method of assigning number-aided cards in grade IV SDN 07 Sepoteng, Bengkayang district. The research method that been used was descriptive method with type of Classroom Action Research. This research was done in 2 cycles. The results of research were obtained (1) The ability of teacher to arrange learning draft from cycle I meeting 1 was 2,84 in cycle II meeting 1 was 3,70 and cycle I meeting 2 was 2,95 in cycle II meeting 2 was 3,72. (2) The ability of teacher to do learning showed increase from cycle I meeting 1 was 2,96 in cycle II meeting 2 was 3,63 and cycle I meeting 2 was 3,18 in cycle II meeting 2 was 3,82. (3) The average of learning outcome of student increased from cycle I meeting 1 with score 33,33 became 77,33 in cycle II meeting 1 and cycle I meeting 2 with score 52,67 became 82,17 in cycle II meeting 2. The used the method of assigning number-aided cards increased the result of students learning outcome. Key words : the learning outcome, the method of assigning number-aided cards